2020
DOI: 10.35940/ijitee.b7281.039520
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ICT Skill Among Vocational School Teachers: A case in West Java, Indonesia

Abstract: vocational education, particularly vocational teachers. The demands of vocational teachers in the digital era to be expected to be able to develop learning skills by using concepts, ideas, and thoughts in solving problems through digital technology, so that teachers are able to integrate digital technology in the learning process. This study aims to analyze the level of ICT skills of vocational teachers in West Java. The data of this study were collected using quantitative methods, questionnaires were given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Alazam et al [39] analysed the skills of 329 teachers, finding significant differences in relation to the use of data analysis software such as Excel, with male teachers achieving higher scores. However, Saripudin et al [40] found contradictory results regarding skills related to use of analysis software (Excel), with no significant differences between the two genders. Sivakumaren et al [41] analysed the digital research skills of 773 academics by gender.…”
Section: Digital Skills For Searching Managing Analysing and Communicatingmentioning
confidence: 99%
“…Alazam et al [39] analysed the skills of 329 teachers, finding significant differences in relation to the use of data analysis software such as Excel, with male teachers achieving higher scores. However, Saripudin et al [40] found contradictory results regarding skills related to use of analysis software (Excel), with no significant differences between the two genders. Sivakumaren et al [41] analysed the digital research skills of 773 academics by gender.…”
Section: Digital Skills For Searching Managing Analysing and Communicatingmentioning
confidence: 99%